Exploring interfacial interactions, dielectric, ferroelectric and piezoelectric properties of ultrahigh molecular weight polyethylene/graphene oxide nanocomposites. Issue 4 (15th November 2022) - Adaval, Akanksha; Subash, Cherumannil K.; Shafeeq, Valiyaveetil H.; Singh, Shiva; Maji, Pradip K.; Aslam, Mohammed; Turney, Terence W.; Simon, George P.; Bhattacharyya, Arup R.
Abstract: Graphene oxide (GO) incorporated ultra‐high molecular weight polyethylene (UHMWPE) nanocomposites were prepared by encapsulating GO by UHMWPE in an aqueous media via high‐shear mixing, which were subsequently dried and compression molded. Morphological characterizations via scanning electron microscopy revealed the intercalation of UHMWPE chains in the graphitic stacks corresponding to GO. Further, dielectric permittivity of UHMWPE/GO nanocomposite of 1 wt% GO showed a drastic increase ( 61) as compared to pure UHMWPE ( 2) due to an enhanced interfacial polarization. A significantly higher value of remnant polarization ( 10 nC/cm 2 ) and coercive field ( 3 kV/cm) was observed in UHMWPE/GO nanocomposite of 1 wt% GO, which showed a strong hysteresis loop of polarization versus electric field plot as compared to pure UHMWPE, which displayed a very weak hysteresis loop. The piezoelectric coefficient ( d 33 ) of 9.5 pm/V was estimated in UHMWPE/GO nanocomposite of 1 wt% GO via piezoresponse force microscopy. Nanocomposite sensor devices were also fabricated and piezoelectric output voltage of 6 V was recorded in UHMWPE/GO nanocomposite of 1 wt% of GO. We report here for the first time the unique ferroelectric and piezoelectric properties displayed by UHMWPE/GO nanocomposites. Abstract : Piezoelectric and Ferroelectric Properties of UHMWPE Based Nanocomposites.